Response to “A Validation Study of the Danish ICD-10 Diagnosis Code K75.0 for Pyogenic Liver Abscess” [Letter] - Akbar PS; Marselina EV (Clinical Epidemiology)
Prima Soultoni Akbar, Elystia Vidia Marselina Medical Record and Health Information Department, Poltekkes Kemenkes Malang, Kota Malang, Jawa Timur, IndonesiaCorrespondence: Prima Soultoni Akbar, Poltekkes Kemenkes Malang, Jl. Ijen 77C, Malang, Indonesia, Email prima_soultoni_akbar@poltekkes-malang.ac.id